ASPECTOS METODOLÓGICOS DE LA ORDENACIÓN DE ENCINARES EN SIERRA MORENA OCCIDENTAL - DOMINGO, J. M.; MARÍN, F. J. (III Congreso Forestal Español, 2001)
This paper presents the analysis of three Management Projects made up for Mediterranean Forest Management Units, mainly composed by evergreen oaks (Quercus ilex ssp. rotundifolia) stands with a low tree density, which are called dehesas. The dehesa is mainly used as range land and normally presents hilly landforms, acidic soils non suitable for agriculture, a temperate-warm climate, and trees covering at least 10% of the surface. It is a man made system which needs work in order to maintain its balance, but it is also a traditional landscape giving highly valued productions. Therefore we must try to find management solutions to preserve an enhance the dehesa systems; one of the greatest problems, tree preservation and renewal is presented here.
The following values have no corresponding Zotero field: periodical: III Congreso Forestal Español pub-location: Granada
Keywords: Dehesa; evergreen oak; Mediterranean forest management